James and the red balloon, and other Thomas the tank engine stories - Awdry, W.; Mitton, David; Palone, Terry; Permane, Terry; Awdry, W. (New York : Random House, 2004)
Thomas and the other engines have various adventures as they learn more about getting along with each other.
"Based on The Railway Series by The Reverend W Awdry."
Keywords: Railroad trains -- Juvenile fiction; Interpersonal relations -- Juvenile fiction